The Laboratory as a Site for Research on Acting: relationships between art and science - Sastre, Martín Fons (Revista Brasileira de Estudos da Presença, 2021)
This article focuses on new knowledge perspectives proposed by research on onstage practice within the performing arts. It is based on the notion of the laboratory as a backbone, methodological framework, and place for exploring research-creation projects. Our study offers critical reflections on research procedures, taking the actor’s creative process as our object of study. We go on to establish a connection between theoretical dimensions and practical expressions, through analysis of two research projects that confront performance practice with its underlying scientific premises. Lastly, different modes for publishing and disseminating the results of research on onstage practice are discussed.